Vote-buying as a moderator variable: The effect of political trust on college student participation in election - Muhammad Arief Sumantri; Suryanto Suryanto (Faculty of Social and Political Science, Universitas Airlangga, 2020)
Considering that the number of college student beginner voters in the Indonesian 2019 General Election has experienced a drastic increase, this research aims to determine the effect of political trust and vote-buying on college students’ political participation in the general elections, partially, and simultaneously. This research was conducted on 348 active college students in Surabaya, using the purposive sampling technique. The scale was used to measure political participation, vote-buying, and the researchers composed the college students’ political trust. The data analysis techniques used to test the research hypotheses were the Hierarchical Regression Test, Moderated Regression Analysis (MRA), and the Andrew Hayes Process. The results of the analysis show that political trust (p=0.038), vote-buying (p=0.001) partially, and simultaneously (p=0.000) affect political participation. Partially, political trust has a positive effect, while on the other hand, vote-buying has a negative effect. In addition, vote-buying is also a significant moderator variable used to strengthen the influence of political trust (β=0.658, t=1.984, p=0.048) among college students concerning political participation. In this study, vote-buying acts as a quasi-moderator because the effect of Z (vote buying) on Y (political participation) and the effect of Z*X1 (vote-buying*political trust) interaction on Y; has been proven to be significant. It can be concluded that political trust positively and significantly influences college students’ political participation in the general elections.